Assessing the impact of feed technology adoption by smallholders in sweet potato-pig systems in Sichuan, China - Lapar, Ma. Lucila; Toan, N.N.; Zou, C.; Liu, J.; Li, X.; Randolph, Thomas F. (2012)
This paper employs propensity score matching (PSM) to examine the impact of sweet potato-based feed technology adoption on household-based pig production in Sichuan, China. An ex post survey in six villages was conducted in 2009. Five villages were in the project intervention sites (experimental group) and one village was not exposed to project intervention (control group). A total of 111 households were randomly selected to represent the exposed areas (experimental group) from the list of households previously interviewed in a baseline survey; and 53 households came from the non-exposed areas (or control group). Average treatment effects were estimated using matching estimators such as nearest neighbour matching (NNM), radius matching (RM), and kernel matching (KM). Results indicate positive net benefit from adoption of sweet potato-based feeding technology, (i.e., gross margin estimates of silage adopters, are on average higher by 2-4 RMB per kg live weight of output than non-adopters of similar characteristics). Silage adopters are also likely to produce 3-7 more slaughter pigs per year than non-adopters having similar characteristics, on average. Analysis of factors driving adoption indicates that sweet potato-based feed technology is not suitable in all smallholder contexts in Sichuan. Overall, the results show that sweet potato-based feed technology plays an important role in helping household-based pig producers become resilient, by having options in feeding strategies that help them cope with volatility in output prices (e.g., prices of live pigs as a function of retail prices of pork) and input prices (e.g., price of corn vis-à-vis price of pork, price of industrial feed). Exposure to the technology and its benefits through actual demonstration also appears to be more effective in engendering uptake and sustaining adoption.